PERLINDUNGAN ANAK KORBAN TINDAK PIDANA INSES DALAM QANUN ACEH NOMOR 6 TAHUN 2014 TENTANG HUKUM JINAYAT - Sarip Hidayat; Beben Muhammad Bachtiar; Anthon Fathanudien,; Bias Lintang Dialog; Erga Yuhandra (IAIN Syekh Nurjati Cirebon, 2023)
Incest is intercourse committed by someone who has blood relations in Indonesian law, incest includes acts that are prohibited by every religion and is included in the types of criminal acts, in the aceh qanun incest includes the qualifications of the type of adultery finger where Uqubat Hudud and Uqubat Ta'zir as someone who does it, the crime of incest often happens to children who are victims of this due to economic factors, social media and the low level of education of people who do it, with the occurrence of this crime it is very important with the existence of the Child Protection Act as legal umbrella for people or victims who commit incest, settlement of legal disputes legal protection of children as perpetrators of criminal acts or victims of incest with Law Number 35 of 2014 amendments to Law Number 23 of 2004 concerning Child Protection and Law Number 11 concerning Justice System a ak then it can be resolved through litigation or non-litigation (Restorative Justice and Diversion).